PENGARUH JIWA KEWIRAUSAHAAN ISLAM, MODAL USAHA DAN LOKASI USAHA TERHADAP TINGKAT LOYALITAS PEMBELI PADA UMKM KUE GETI LUCKY’S SUMBER GEMPOL, TULUNGAGUNG - Siti Hajar; Agus Eko Sujianto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine how the influence of the Islamic entrepreneurial spirit, business capital and business location on buyer loyalty at the UMKM Kue Geti Lucky's Sumbergempol, Tulungagung. The research method used by the researcher using quantitative-descriptive methods using primary data obtained by distributing questionnaires randomly and processed using the SPSS statistical test. The dependent variable used in this study is buyer loyalty, while the independent variables in this study are the Islamic entrepreneurial spirit, business capital and business location. Based on this research, the results obtained are tcount < table or 0.952 < 1.984, the significant value generated is 0.343 > 0.025. Therefore, the two variables of Islamic entrepreneurial spirit and business location on buyer loyalty in MSMEs, Lucky's Cakes, Tulungagung have no effect, but if we count one -one result obtained will be significant. For one variable of venture capital, the value of tcount > t table or 6.516 > 1.984 and the resulting significance value of 0.000 < 0.025 on buyer loyalty to MSMEs, Lucky's Cakes, Tulungagung. And from the results of the value fcount > ftable or 19,501 > 3.09, the significant value produced is 0.000, which is smaller than the level of significance of 0.05, all variables have a significant effect.